Persepsi Masyarakat terhadap Pemberitaan Kasus Jual Beli Organ Tubuh di Media Online - Yusmiana, Yusmiana; Yusuf, Raidah Intizar (Journal Proxemics, 2024)
This study uses a qualitative method with in-depth interviews. The purpose of this study is to determine public perception of negative content that occurs in organ trading cases in Makassar City in terms of social aspects, moral aspects and mental aspects of society and to find out what the government (Makassar Communication and Information Service) and society do in order to prevent (preventive) and handle (curative) the impact of negative content. From the results of the study, the organ trading case that occurred in Makassar gave rise to public perceptions that showed that negative content on social media has a broad and serious impact on various aspects of people's lives. Exposure to negative content can damage the mental, moral, and social health of social media users. Researchers also found that the lack of literacy processes in the community resulted in a lack of supervision of children and their surroundings. This also highlights the role of government in overseeing people's access rights on social media, as well as minimizing negative content that can harm both children and adults. In addition, with better awareness and control from parents, as well as strict regulatory support, it is hoped that it can reduce the risk of spreading negative content and protect society from the negative impacts of uncontrolled information technolo